From "Smaller is Stronger" to "Size‐Independent Strength Plateau": Towards Measuring the Ideal Strength of Iron. (17th April 2015) - Han, Wei‐Zhong; Huang, Ling; Ogata, Shigenobu; Kimizuka, Hajime; Yang, Zhao‐Chun; Weinberger, Christopher; Li, Qing‐Jie; Liu, Bo‐Yu; Zhang, Xi‐Xiang; Li, Ju; Ma, Evan; Shan, Zhi‐Wei
<x xml:space="preserve">Abstract</x> The trend from "smaller is stronger" to "size‐independent strength plateau" is observed in the compression of spherical iron nanoparticles. When the diameter of iron nanospheres is less than a critical value, the maximum contact pressure saturates at 10.7 GPa, corresponding to a local shear stress of ≈9.4 GPa, which is comparable to the theoretical shear strength of iron.